2022
DOI: 10.3389/fonc.2022.935817
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Conversion therapy for advanced intrahepatic cholangiocarcinoma using PD-1 inhibitor plus S-1 and nab-paclitaxel

Abstract: Intrahepatic cholangiocarcinoma (iCCA) is a highly malignant hepatobiliary tumor with a high rate of advanced disease at initial presentation. Conversion into resectable iCCA is important for improving the prognosis. Immunotherapy-based regimens are being increasingly used for treating advanced iCCA in recent years. However, the use of combined chemotherapy and immunotherapy for conversion has rarely been reported. The aim of this report was to present the outcomes of a 52-year-old female patient with IIIB iCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Li et al found that PD-1 inhibitor combined with S-1 and nab paclitaxel can be used to achieve the transformation treatment of advanced refractory CCA. This combination therapy is safe and effective, and can significantly prolong the survival of patients (54). Previous evidence suggested that PD-1 inhibitors are suitable for patients who have high TMB, high microsatellite instability (MSI-H), deficient mismatch repair (dMMR), and PD-L1 positive expression.…”
Section: Pd-1 and Pd-l1 Inhibitorsmentioning
confidence: 99%
“…Li et al found that PD-1 inhibitor combined with S-1 and nab paclitaxel can be used to achieve the transformation treatment of advanced refractory CCA. This combination therapy is safe and effective, and can significantly prolong the survival of patients (54). Previous evidence suggested that PD-1 inhibitors are suitable for patients who have high TMB, high microsatellite instability (MSI-H), deficient mismatch repair (dMMR), and PD-L1 positive expression.…”
Section: Pd-1 and Pd-l1 Inhibitorsmentioning
confidence: 99%